Metode, Model dan Pendekatan Evaluasi dalam Pendidikan Islam - M. Darul Ilmi; M. Yahya Ashari (Jurnal Budi Pekerti Agama Islam, 2024)
This article aims to analyze the Methods, Models, and Approaches to Evaluation in Islamic education. The research employs a literature review method, gathering data from relevant books, journals, and scholarly articles. Content analysis is used to classify the data, and evaluation is conducted to summarize and explain the findings. In the field of Islamic education evaluation, the evaluation models used encompass several approaches outlined by experts. These models include the Goal Oriented Evaluation Model, Goal Free Evaluation Model, Formative Summative Evaluation Model, and Countenance Evaluation Model. Additionally, evaluation methods in Islamic education involve both test and non-test techniques, with tests categorized into diagnostic tests, formative tests, and summative tests. Non-test techniques include rating scales, questionnaires, matching lists, interviews, observations, and life histories. The article also explains the approach to Islamic education evaluation from a learning perspective, covering formative evaluation, summative evaluation, and placement evaluation. This approach refers to the viewpoint on the evaluation process and provides a theoretical foundation for the implementation of appropriate evaluation methods.